Agonale Invektivität Konstellationen und Dynamiken der Herabsetzung im italienischen und deutschen Humanismus - Israel, Uwe; Kraus, Marius; Sasso, Ludovica (Das Mittelalter. Perspektiven mediävistischer Forschung. Beihefte, 2021)
What does humanism mean, who is a humanist? Contemporaries clarified this not least through diatribes. Intellectuals who, since the middle of the fourteenth century, have regarded rhetoric as the most noble method of promoting virtue, searching for truth and knowledge of God, saw mutual personal degradation as the means of asserting their positions.